2011
DOI: 10.1111/j.1748-3743.2010.00235.x
|View full text |Cite
|
Sign up to set email alerts
|

Management of person with dementia with aggressive and violent behaviour: a systematic literature review

Abstract: To communicate with people with dementia provides a challenge for nurses and other health caregivers. To satisfy the needs of good nursing care, an important aspect is therefore to get knowledge and understanding about aggressive and violent behaviour and its management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
68
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(71 citation statements)
references
References 57 publications
2
68
0
1
Order By: Relevance
“…Assault may include being hit, kicked, pinched, shoved, grabbed, or bitten. Assaults in this context may also include believable threats to the caregiver(s), or physical aggression against property which could induce fear of assault or danger to the caregiver (Galinsky et al, 2010; Shah, 1995; Ryden, 1988; Enmarker, Olsen, & Hellzen, 2011; Kunik et al, 2010). Note that “agitation” is not necessarily “aggression.” These two concepts are not always clearly separated in the literature, but while agitation generally implies verbal or physical behaviors related to discomfort or confusion, aggression clearly implies hostile physical motion, regardless of the trigger or intent.…”
Section: Definitions Incidence and Correlations To Premorbid Personmentioning
confidence: 99%
See 2 more Smart Citations
“…Assault may include being hit, kicked, pinched, shoved, grabbed, or bitten. Assaults in this context may also include believable threats to the caregiver(s), or physical aggression against property which could induce fear of assault or danger to the caregiver (Galinsky et al, 2010; Shah, 1995; Ryden, 1988; Enmarker, Olsen, & Hellzen, 2011; Kunik et al, 2010). Note that “agitation” is not necessarily “aggression.” These two concepts are not always clearly separated in the literature, but while agitation generally implies verbal or physical behaviors related to discomfort or confusion, aggression clearly implies hostile physical motion, regardless of the trigger or intent.…”
Section: Definitions Incidence and Correlations To Premorbid Personmentioning
confidence: 99%
“…There are a number of things which have been correlated in the literature as triggers for violence, including: pain, reduced vision and/or hearing, changes in the environment, excessive noise or activity, locked doors, limited privacy or space, and quality of relationship with caregivers (Enmarker, Olsen, & Hellzen, 2011; Kunik et al, 2010). Depression and premorbid aggressive personality traits may also be related to aggressive or violent behavior (Enmarker, Olsen, & Hellzen, 2011; Kunik et al, 2010; O'leary, Jyringi & Sedler, 2005).…”
Section: Triggers To Violence and Issues Of Homecare And Healthcare Sermentioning
confidence: 99%
See 1 more Smart Citation
“…Limited literature exists examining staff responses to aggressive resident behavior in long-term care facilities (Enmarker, Olsen, & Hellzen, 2011), but we know of no research evaluating the relative frequency of staff-reported actions and strategies to manage R-REM. The goal of our research was to more completely describe and characterize current nursing home staff experience with and responses to R-REM.…”
mentioning
confidence: 99%
“…(Cohen-Mansfield et al , 1990;Enmarker et al, 2011;Soreff & Siddle, 2003,) Enmarker et al in the landmark article, Management of person with dementia with aggressive and violent behaviour: a systematic literature review wrote "The results could be summarized in two themes: 'origins that may trigger violence' and 'activities that decrease the amount of violent behaviour'. Together, the themes showed that violence was a phenomenon that could be described as being connected to a premorbid personality …" (Enmarker et al, 2011, pp.…”
Section: Personality Elements and Gender Issuesmentioning
confidence: 99%